PENGUATAN LABORATORIUM BANK SYARIAH UNTUK MENDUKUNG PERKEMBANGAN INDUSTRI KEUANGAN SYARIAH - Zuhroh, Idah (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
Islamic banking in the last two decades has grown rapidly. This rapid progress is inseparable from the government attempts to makeIslamic banking Islamic financial world as a trendsetter. However, tomake Indonesian Islamic banking as a trendsetter Islamic finance in Asia still faces obstacles, especially the availability of human resources from theuniversity. Role of the real banking Laboratory very urgent to provide a source for learning as well associalization media education on academic community . This paper seeks toprovide an overview based on the author?s experience to establish a laboratory, starting from the pioneering phase to the technical implementation of the synergy with student learning model.